Somethings go together - Zolotow, Charlotte, 1915-; Gundersheimer, Karen (New York : HarperFestival, 1969)
Illustrations accompany couplets describing things that go together naturally, such as "Sand with sea" and especially "you with me."
Keywords: Children's poetry, American; American poetry